Integration of AI and Telehealth Technology in the NERS Curriculum: Answering the Global Healthcare Challenges - Lestari, Inka (Fakultas Ilmu Kesehatan Universitas Gresik, 2025)
This research is driven by the need to integrate artificial intelligence (AI) and telehealth technologies into the nursing education curriculum to prepare competent healthcare professionals for the challenges of global health services. The aim of this study is to explore and analyze how the implementation of these technologies can enhance the quality of nursing students' competencies. The research employs a quantitative approach with a descriptive-exploratory design, involving 10 universities that have integrated AI and telehealth into their nursing curricula. Data were collected through surveys of students and faculty, as well as interviews with program heads and healthcare professionals. The results indicate that although the adoption of AI and telehealth in nursing education has increased, its implementation is still limited to elective courses and simulations. Furthermore, these technologies have shown to enhance students' communication skills with patients and their ability to analyze medical data, but there are challenges in applying these skills in clinical settings. The study also identifies the lack of training for faculty and inadequate infrastructure as the primary barriers to successful implementation. The findings of this study are expected to provide recommendations for the development of nursing curricula that are more aligned with technological advancements.